2022
DOI: 10.1051/0004-6361/202142527
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic rays and thermal instability in self-regulating cooling flows of massive galaxy clusters

Abstract: One of the key physical processes that helps prevent strong cooling flows in galaxy clusters is the continued energy input from the central active galactic nucleus (AGN) of the cluster. However, it remains unclear how this energy is thermalised so that it can effectively prevent global thermal instability. One possible option is that a fraction of the AGN energy is converted into cosmic rays (CRs), which provide non-thermal pressure support, and can retain energy even as thermal energy is radiated away. By mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 126 publications
1
7
0
Order By: Relevance
“…In agreement with the linear analysis of Kempski and Quataert ( 2020 ), non-linear simulations of thermal instability development in the ICM in the presence of AGN feedback heating and CRs demonstrate that CRs are initially unable to stabilize most of the hot and dilute plasma against TI (i.e., the gas is mostly characterized by and ; Beckmann et al. 2022a ). However, once the gas has cooled out of the hot phase, it either settles down to a thermally stable state with , or to a state where but and further collapse can be prevented by significant CR pressure (see Fig.…”
Section: Astrophysical Systemssupporting
confidence: 73%
See 2 more Smart Citations
“…In agreement with the linear analysis of Kempski and Quataert ( 2020 ), non-linear simulations of thermal instability development in the ICM in the presence of AGN feedback heating and CRs demonstrate that CRs are initially unable to stabilize most of the hot and dilute plasma against TI (i.e., the gas is mostly characterized by and ; Beckmann et al. 2022a ). However, once the gas has cooled out of the hot phase, it either settles down to a thermally stable state with , or to a state where but and further collapse can be prevented by significant CR pressure (see Fig.…”
Section: Astrophysical Systemssupporting
confidence: 73%
“…15 in Beckmann et al. 2022a ). Such significant pressure support ( ) in the cold phase is expected even if the initial in the hot phase because of adiabatic compression of CRs combined with dramatic loss of thermal pressure due to radiative cooling.…”
Section: Astrophysical Systemsmentioning
confidence: 92%
See 1 more Smart Citation
“…We have ignored the effect of important physics such as magnetic fields (Hopkins et al 2020;Wang et al 2021;Buie et al 2022), cosmic rays (Butsky et al 2020;Kempski & Quataert 2020;Beckmann et al 2022), and conduction (Parrish et al 2009;El-Badry et al 2019), see Faucher-Giguère & Oh (2023) for a review. Magnetic fields and cosmic rays are expected to be energetically important and can affect the properties of the thermal energy-driven outflow.…”
Section: Physicsmentioning
confidence: 99%
“…More recently, the properties of CRp dominated jets have also seen growing attention in the literature (e.g. Mathews & Brighenti 2008;Guo & Mathews 2011;Ruszkowski et al 2017;Ehlert et al 2018;Yang et al 2019;Su et al 2021;Beckmann et al 2022). These works have demonstrated that differences in the energy content of AGN bubbles could lead to very different heating impacts and dynamical evolution of the ICM.…”
Section: Introductionmentioning
confidence: 99%